(3JQLeI cJGH CJhdhLjGs - (3JQLeI (B/ (3fbd YHO GdeSjM Hf YHO Gddg Hf fGYe GdMeUjs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdLRA GdChd ef cJGH GQSWhWGdjS GdajdSha GdeSei HGdjhfGfjI CKhdhLjG hgh Gdbhd Ydi GdQHhHjI s
(3BNQgG (B:s
(3Ke bHdJ UhQI GdGSWbHSGJ Ke bHdJ Yf Jdc GdUhQI Je cJGH GfhdhLjG ddeYde GdChd GQSWhWGdjS HJhajb Gddg hYhfg hcQeg s
(3HgG fXGe GdJYbjHIs
(3JQLeI YHO GdeSjM Hf YHO Gddg Hf fGYe GdMeUi hCUdMg GdcfOis
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3SHMGf Gddg HLGeYI YdjcQI s
Keywords: (3GdadSaI hGdefWbs